PILIHAN RASIONAL BURUH TANI DALAM MEMILIH TPQ SEBAGAI PENDIDIKAN AGAMA ANAK DI DESA TAMBONG KABUPATEN BANYUWANGI - Dina Rizqayanti; Dodik Harnadi; Jati Arifiyanti (JOURNAL SAINS STUDENT RESEARCH, 2025)
This research was conducted in Tambong Village, Banyuwangi Regency, to understand the rationale behind choosing the Al-Qur'an Education Park (TPQ) as a religious education institution for their children. Using a qualitative phenomenological approach and Michael Hechter's Rational Choice Theory, the study found that the choice of TPQ was not solely based on tradition, but also on rational considerations such as affordability, proximity, and trust in the quality of the religious teachers (ustadz and ustadzah). The time-consuming working conditions of farm laborers also encouraged the TPQ to be viewed as a practical and effective option. This decision reflects an evaluation of benefits, value, and affordability within the economic and social constraints of rural families.